LEXICAL AND GRAMMATICAL MEANINGS OF TRADITIONAL GAME SONG LYRICS IN TASIKMALAYA - Irma Rahmawati; Muhammad Irgi Fahrezi; Neng Aropah Wasilah; Aveny Septi Astriani (JOURNAL OF HUMANITIES AND SOCIAL STUDIES, 2023)
This research aims to determine the lexical meaning and grammatical meaning of the lyrics of traditional game songs including oray-orayan, cingciripit, and perepet jengkol. This game is one of the traditional games in Tasikmalaya, West Java. The method used in this research is a qualitative descriptive method. The results of this research indicate that the lyrics of the songs oray-orayan, cingciripit, and perepet jengkol have lexical meaning and grammatical meaning contained therein. The song lyrics are in Sundanese which were translated into Indonesian.